Papillomavirus vaccine in Peru - Venegas Rodríguez, Gino (2020)
Cervical cancer is a public health concern. The human papillomavirus (HPV) vaccine protects against infection with HPV. The vaccine has been shown to be effective in preventing premalignant lesions and cervical cancer, as well as lesions of the vulva, vagina, anal canal, penis, and oropharynx. It has also proven to be cost effective and supports the idea of introducing a national vaccination strategy. The HPV vaccine could be the ideal tool for health systems where secondary prevention has not been successful over time. The implementation of the vaccination program in Peru began in 2011. Currently, in Peru, the indication for vaccination is with the quadrivalent vaccines for 5th grade girls from public and private schools. It is administered in 2 doses, 0-6 months. In 2019, coverage in Peru was 87% (234 535 girls) for the first dose and 78% (211 339 girls) for the second dose.